Magnetocaloric Effect in 3D Gd(III)-Oxalate Coordination Framework - Fang-Wen Lv; Mei-Xin Hong; Xue-Ting Wang; Haiquan Tian; Chun-Chang Wang; Xiu-Ying Zheng (Nanomaterials)
Cryogenic magnetic refrigerants based on the magnetocaloric effect (MCE) hold significant potential as substitutes for the expensive and scarce He-3. Gd(III)-based complexes are considered excellent candidates for low-temperature magnetic refrigerants. We have synthesized a series of Ln(III)-based metal-organic framework (MOF) Ln-3D (Ln = Gd/Dy) by the slow release of oxalates in situ from organic ligands (disodium edetate dehydrate (EDTA-2Na) and thiodiglycolic acid). Structural analysis shows that the Ln-3D is a neutral 3D framework with one-dimensional channels connected by [Ln(H2O)3]3+ as nodes and C2O42− as linkers. Magnetic measurements show that Gd-3D exhibits very weak antiferromagnetic interactions with a maximum −ΔSm value of 36.6 J kg−1 K−1 (−ΔSv = 74.47 mJ cm−3 K−1) at 2 K and 7 T. The −ΔSm value is 28.4 J kg−1 K−1 at 2 K and 3 T, which is much larger than that of commercial Gd3Ga5O12 (GGG), indicating its potential as a low-temperature magnetic refrigerant.